Plan de marketing para la comercialización de cinco hortalizas orgánicas de hojas, en el cantón El Empalme, provincia del Guayas. año 2015 - Velásquez Morales, Jesenia Amelia (2015)
The project presented demonstrates the development of the marketing plan for the marketing of five organic leafy vegetables in Canton El Empalme, allowing assistance project customers stores, commissaries and vegetable fairs of the town, featuring a variety of organic vegetables, so not knowing organic vegetables the inhabitants of the village of El Empalme not increase profits while maintaining the low position to the other competitors, therefore, it is necessary to have adequate information to increase patronage, since in this market variety of organic products, the challenge comes to position the vegetables through research in the field with a series of questions to determine the supply and demand of the economically active population for 2015 is 40174 inhabitants 382 obtaining as proportional sample surveys, identifying marketing channels in the target market, making SWOT analysis as an opportunity to obtain an increasing demand for organic vegetables consumption in the canton El Empalme, translating the findings and recommendations through the tabulation the results obtained accurate information as possible with real data, so therefore the hypothesis through checks, marketing five leaves and organic vegetables, chard, turnip, green cabbage, purple cabbage and broccoli provides high purchase consumers in the canton El Empalme, 2015 and that 69% of the target if they are willing to pay a higher price for a vegetable that is certified as organic. The marketing plan to publicize the five leafy vegetables can increase demand in the market and attract customers by developing marketing strategies that indicate the marketing mix of organic leafy vegetables ORGANILEAFY like chard, turnip, green cabbage , red cabbage and broccoli in the canton El Empalme Guayas province.